Jurnal Riset dan Inovasi Peternakan - Adhianto, Kusuma (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2024)
Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals) Chief Editor Kusuma Adhianto Associate Editor Ratna Ermawati Etha‘ Azizah Hasiib Dian Kurniawati Teguh Rafian Editorial Board Dian Septinova Farida Fathul Ali Husni Erwanto Riyanti Syahrio Tantalo Khaira Nova Sri Suharyati Purnama Edy Santosa Siswanto Liman